2019
DOI: 10.1080/09637486.2019.1689547
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum aflatoxin concentrations and the nutritional status of children aged 6–24 months from Zambia

Abstract: In Zambia, mothers/caregivers feed their children cereal-based complementary foods that are prone to aflatoxin contamination. This study evaluated the relationship between exposure to aflatoxins and the nutritional status of young children. It covered 400 mothers with children aged 6-24 months. Their nutritional status assessed by measuring weight and height using standard procedures. Serum samples analysed for aflatoxin B1-lysine (AFB1-lys), a reliable biomarker of aflatoxin exposure. Child sickness and age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
12
0
2
Order By: Relevance
“…However, there are many gaps in the knowledge of doses, mechanisms, and outcomes of exposure to aflatoxins in pregnant women (Benkerroum, 2020). Elevated levels of AFs adduct are commonly noticed in malnourished and stunted children (Alamu et al, 2020;Coulter et al, 1986). Based on the exposure levels found in this study, risk related to the occurrence of these effects in Serbian population is most likely low.…”
Section: Tablementioning
confidence: 71%
“…However, there are many gaps in the knowledge of doses, mechanisms, and outcomes of exposure to aflatoxins in pregnant women (Benkerroum, 2020). Elevated levels of AFs adduct are commonly noticed in malnourished and stunted children (Alamu et al, 2020;Coulter et al, 1986). Based on the exposure levels found in this study, risk related to the occurrence of these effects in Serbian population is most likely low.…”
Section: Tablementioning
confidence: 71%
“…One FGD was conducted from each ward among mothers/caregivers of children 6–23 months of age to understand how they handled sorghum and if mycotoxin contamination was of concern when handling children's food. Children aged 6–23 months are nutritionally vulnerable and the introduction of complementary foods that are contaminated with mycotoxins could further impair their growth and development (Alamu et al., 2020 ). Therefore, it was of importance to have a focus group discussion with the mothers/caregivers of children 6–23 months of age.…”
Section: Methodsmentioning
confidence: 99%
“…In some countries, mainly in Africa and Asia, children become fed almost exclusively with potentially contaminated grain, and after being weaned, this is due to the economic condition. It was shown that the increase in serum concentration of aflatoxin in these children is also related to dwarfism (Alamu et al, 2020).…”
Section: Aflatoxinsmentioning
confidence: 99%